ANALISIS KONSENTRASI SPASIAL DAN KEKUATAN AGLOMERASI INDUSTRI KECIL MAKANAN OLAHAN DI KABUPATEN SEMARANG - Nur Chollidah (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2012)
The purposed of this studied was to analyzed the location of small food processing industry in Semarang, identified the amount of agglomeration power in a small industrial foods processed that were concentrated in the district of Semarang and described specialized of small industry of food processing in District of Semarang in accordance with the potential of the region.The population of this research is the sub-district in Semarang Regency. The method of accumulating data used are documentation and interview method. The analysis used the Herfindahl Index, locational Gini index, an index of strength of agglomeration and descriptive analysis. Based on the research results of small food processing industry was concentrated in the districts Tuntang of 0,2419 which is the contribution of labor by 49.19% of the districts in Semarang district. The amount of power that occurred in the agglomeration of small food processing industry was concentrated in Semarang district amounted to 0.069856, with the level of small food processing industry specialization by 0.070254. Policy planning and development of small industries considered strategic processed food is the cluster approach. Cluster will increase bargaining power and more profitable, not only the price but also the efficiency of regional economic development